Apremilast survival and reasons for discontinuation in psoriasis: five-year experience from a Greek tertiary care centre - Elena Sotiriou; Aikaterini Tsentemeidou; Nikolaos Sideris; Aimilios Lallas; Nikolaos Kougkas; Dimitrios Ioannides; Efstratios Vakirlis (Dermatology Practical & Conceptual, 2022)
Introduction: Drug survival is an indirect measure of efficacy and safety and its post-marketing assessment using real-life data is invaluable.